2012
DOI: 10.1093/ckj/sfs036
|View full text |Cite
|
Sign up to set email alerts
|

Chickenpox infection after renal transplantation

Abstract: Background.Chicken pox, although a common infection among children, is rare in immunocompromised patients, particularly renal transplant recipients, and carries a very high incidence of morbidity and mortality There is little data on chickenpox in adult renal transplant recipients, although reports have suggested that it may follow a virulent course requiring frequent hospitalization, and in severe cases can cause death.Aims.To evaluate the incidence, severity and complications of a varicella/chickenpox infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 16 publications
0
23
1
2
Order By: Relevance
“…Varicella infection is a potentially serious event in an immunocompromised patient, with possible complications including pneumonia, hepatitis, and encephalitis . For this reason, documentation of immunity by vaccination is strongly encouraged in transplant candidates, as far as is practical and possible.…”
Section: Discussionmentioning
confidence: 99%
“…Varicella infection is a potentially serious event in an immunocompromised patient, with possible complications including pneumonia, hepatitis, and encephalitis . For this reason, documentation of immunity by vaccination is strongly encouraged in transplant candidates, as far as is practical and possible.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, disseminated Lyme disease has rarely been reported to cause orchitis . In solid organ transplant recipients, orchitis is a rare clinical presentation and has been reported in renal transplant patients secondary to chickenpox and tuberculosis, in a pediatric liver transplant patient due to Listeria monocytogenes and in a cardiac transplant recipient due to Nocardia asteroides . Differential diagnosis for transplant patients presenting with febrile illness, leukopenia, and thrombocytopenia is wide and includes mainly viral infections such as Cytomegalovirus , Parvovirus B19, Human herpes virus 6 and Human herpes virus 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the introduction of acyclovir the overall mortality rates was 34% [ 22 ]. One ten year retrospective analysis of renal allograft patients showed that varicella associated with an increased mortality of 13.4% [ 23 ]. To our knowledge and review of literature, there were no reports on mortality rates among patients with ESRD on dialysis and ESRD not on renal replacement therapy for direct comparison.…”
Section: Discussionmentioning
confidence: 99%